The Kaiparowits Puebloans: Kayentan or Virgin Branch Migrants?. Issue 4 (2nd October 2019) - Geib, Phil R.
Abstract : More than 50 years ago archaeologists identified a high-density of small Puebloan habitations on the Kaiparowits Plateau in southern Utah. Analysis of pottery from these habitations by James Gunnerson and Florence Lister resulted in conflicting interpretations of cultural affiliation. Gunnerson argued for a Virgin affiliation whereas Lister argued for a Kayentan affiliation. Lister's interpretation triumphed and the Puebloan occupation of the Kaiparowits was attributed to a migration of Kayenta people from the south during the late Pueblo II period. A review of architectural and artifactual evidence fails to support a Kayentan migration. An expansion of Puebloan groups from the west and southwest better accords with the archaeological record on the Kaiparowits Plateau.